2022
DOI: 10.1039/d1ta10652j
|View full text |Cite
|
Sign up to set email alerts
|

The BaCe0.16Y0.04Fe0.8O3−δ nanocomposite: a new high-performance cobalt-free triple-conducting cathode for protonic ceramic fuel cells operating at reduced temperatures

Abstract: Compared with conventional oxygen-ion-conducting solid oxide fuel cells (O-SOFCs), proton ceramic fuel cells (PCFCs) are more attractive for low-temperature operation due to the smaller activation energy and higher ionic conductivity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 116 publications
(51 citation statements)
references
References 81 publications
2
32
1
Order By: Relevance
“…Table 1 lists some results to compare the performance of this study with the reported literatures. The peak power density of the single cell at 600°C tested by the powder prepared via the wet chemical method in the literature is ~450 mW cm −2 (cathode exposed to static air), 29 This result is larger than the performance measured in this study, which should be attributed to the smaller particle size and the larger specific surface area in their study.…”
Section: Resultscontrasting
confidence: 67%
See 2 more Smart Citations
“…Table 1 lists some results to compare the performance of this study with the reported literatures. The peak power density of the single cell at 600°C tested by the powder prepared via the wet chemical method in the literature is ~450 mW cm −2 (cathode exposed to static air), 29 This result is larger than the performance measured in this study, which should be attributed to the smaller particle size and the larger specific surface area in their study.…”
Section: Resultscontrasting
confidence: 67%
“…According to the results of thermogravimetric analysis, we calcined the powder at a temperature above 1000°C to analyze the formation of the phase structure of the powder. It has been reported in the literature that BCYF powder with triple conducting ability will eventually form conformal oxides, which are heterogeneous nanocomposites 29 . Figure 2a shows the XRD results of the powder after calcination at 1000, 1050, 1100, 1050, and 1200°C for 10 h. Green powder without sintering is also listed in Figure 2a for comparison (labeled RT).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, a single SOFC is made up of an anode and a cathode, which are separated by an electrolyte 6,7 . Low‐cost and long‐term stable electrode materials are highly desirable for the commercial application of SOFCs within the operating temperature of 600–800°C, or even below 600°C 8–12 . However, SOFCs operating at lower temperatures can unfortunately lead to the poor cell performance, which can be attributed to the increase of cathodic polarization losses 13 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Normally, a single SOFC is made up of an anode and a cathode, which are separated by an electrolyte. 6,7 Low-cost and long-term stable electrode materials are highly desirable for the commercial application of SOFCs within the operating temperature of 600-800 C, or even below 600 C. [8][9][10][11][12] However, SOFCs operating at lower temperatures can unfortunately lead to the poor cell performance, which can be attributed to the increase of cathodic polarization losses. 13 The low ion conductivity of the traditional cathode material La 0.8 Sr 0.2 MnO 3 (LSM) stimulates great efforts at the moment on cobalt-containing mixed oxygen ionic and electronic conductors (MIECs) because of their excellent electrocatalytic activity and high electrical conductivity towards oxygen reduction reaction (ORR) at intermediate temperatures (IT) 14,15 and thus can be served as active cathodes for IT-SOFCs.…”
Section: Introductionmentioning
confidence: 99%